PENERAPAN INKUIRI TERBIMBING PADA HASIL BELAJAR KOGNITIF SISWA KELAS VII A SMPN 3 TANJUNG DALAM KONSEP EKOSISTEM - Almira Ulimaz (Universitas Islam Balitar, 2016)
This study is aimed at seeing how process of improvement of cognitive learning achievement on ecosystem instruction using guided inquiry model. This study used Classroom Action Research with two cycles conducted in four meetings. The subject of the study was the 20 students of grade VII of SMPN 3 Tanjung, South Kalimantan. Data were collected using test and scores of pretest and posttest were used for analysis. Data were analyzed both in quantitative and qualitative forms. The study revealed that guided inquiry model improves cognitive achievement of the VII graders of SMPN Tanjung.